2022
DOI: 10.7150/thno.72317
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiated Schwann cell-derived TGF-β3 is essential for the neural system to promote wound healing

Abstract: Rationale: Wound healing is among the most complicated physiological processes and requires the synchronization of various cell types with distinct roles to re-establish the condition of the original skin. Patients affected by peripheral neuropathies often experience failure to heal. Loss of Schwann cells (SCs), a crucial population of peripheral nervous system cells in skin, may contribute to chronic wounds. However, the role of SCs in wound healing are poorly understood. Methods: The activity of SCs was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The potential signaling activation by MY-1 in keratinocytes was then investigated. It was reported that numerous signaling pathways were involved in the re-epithelialization process, among which Wnt, TGF-β/Smads, and PI3K/AKT signaling were studied in depth [ 29 , 33 36 ]. For PTH and analogs, however, the potential downstream signaling pathways by which they activated keratinocytes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The potential signaling activation by MY-1 in keratinocytes was then investigated. It was reported that numerous signaling pathways were involved in the re-epithelialization process, among which Wnt, TGF-β/Smads, and PI3K/AKT signaling were studied in depth [ 29 , 33 36 ]. For PTH and analogs, however, the potential downstream signaling pathways by which they activated keratinocytes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We found that, unlike that in SCs from wounded normal control mice, the expressions of p75 and c-jun, induced markers of the repair cell phenotype, were delayed in SCs at the wound site after skin injury of diabetic mice. Similarly, Pierson et al ( Ou et al, 2022 )found that the expression of p75 in SCs was delayed and attenuated in diabetic rats after sciatic nerve crush injury, which may contribute to impaired peripheral nerve regeneration. Similar to our study, Ou et al (2022) found that fewer dedifferentiated SCs recognized by Sox2 expression were observed in the mice with streptozotocin (STZ)-induced diabetes (C57-STZ) wounds than in the C57 wounds, which indicated dysfunction of SC repair responses during diabetic wound healing.…”
Section: Discussionmentioning
confidence: 89%
“…Multiple genes are reported to be unregulated, and numerous transcriptional pathways are activated during SC reprogramming. The primary players that control and regulate the repair processes include c-Jun, the mitogen-activated protein kinase (MAPK) pathways, Sonic Hedgehog (Shh), chromatin modifications, Wnt signaling, and the Raf/MEK/ERK signaling pathway ( Napoli et al, 2012 ; Nocera and Jacob, 2020 ; Ou et al, 2022 ). A crucial transcription factor in the reprogramming of the SC and the response to peripheral nerve damage is c-Jun.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the development-like transcriptional state of SCs is also identified in dermal regeneration. The deficiency of dedifferentiated SCs (dSCs) exists in diabetic wounds both in mice and humans, and increasing dSC activity through TGF-β3 can promote early wound healing [ 32 ]. Contrasted to normal skin, the number of SCs significantly increases in keloid as well as surrounding skins.…”
Section: Schwann Cellsmentioning
confidence: 99%